How do scientists model humanness? A qualitative study of human organoids in biomedical research. (March 2023) - Hinterberger, Amy; Bea, Sara
Abstract: We investigate how changes in biotechnology are transforming the pursuit of human-specific models of disease and development. Our case study focuses on scientists who make human organoids. Organoids are stem cell-based three-dimensional multicellular living systems, made in labs, that mimic the function of human organs. Organoids create new opportunities for human health research, but we know little about how researchers understand the relationship between these model systems and the humans they are meant to represent. By analysing 25 interviews, complemented by observation and documentary research conducted in 2020–2022, we identify and discuss four themes that characterize how researcher's model humanness in organoids. For scientists, organoids are powerful tools to approximate the biology of human beings because they represent the closest thing to undertaking experiments on living humans, not previously possible. As laboratory tools, human organoids may replace the need for experimentation on animals, potentially contributing to the 3Rs of animal research (replacement, reduction, and refinement). Humanness is partly operationalized by modelling different human characteristics within organoids, such as male and female, different disease states, age, and other attributes. We find that human organoids are opening up previously closed spaces of experimentation and modelling in biomedicine. We argue that the humanness of organoid model systems are not a given but are enacted with and through a variety of scientific practices. These practices require critical attention from social scientists as the enactments of humanness being modelled in organoids have the potential to shape what and who counts as human in biomedical research. Highlights: Investigates human organoids which are poised to transform biomedicine. First qualitative study on researchers' perspectives of human relevant organoids. Analyses 25 interviewees framings of humanness in organoid systems. Finds that organoids are unlikely to fully replace animals used in research. Argues that the humanness of organoid model systems is not a given but is achieved.